Evaluation of Selection of Public Transport Mode Corridor Blok M – Bundaran Hotel Indonesian in the New Normal Era with Stated Preference - Andri Irfan Rifai; Martindo Gita Dwi Putra; Muhammad Isradi; Amar Mufhidin; Joewono Prasetijo (LPPM of NAROTAMA UNIVERSITY, 2022)
Purpose: Transportation is one of the important things in supporting community activities outside the home. Currently, people are faced with the new normal era so they have to adapt to new things due to the COVID-19 pandemic outbreak. This study wants to know about the behavior of the community in the selection of public transportation in the corridor Blok M – Bundaran Hotel Indonesia in the new normal era. Design/methodology/approach: Data were obtained from the results of a questionnaire survey of users of the Blok M – Bundaran Hotel Indonesia public transport corridor using stated preference methods and used influence attributes in the form of travel costs, travel time, and waiting time. The survey results were collected and then linear regression analysis was performed and modeling was performed using the binomial logit model. Data analysis was carried out from questionnaire data distributed to 100 respondents. Findings: The survey results were collected and then linear regression analysis was performed and modeling was performed using the binomial logit model. Data analysis was carried out from questionnaire data distributed to 100 respondents. The results of linear regression analysis using the SPSS program obtained a mode selection model, namely (UMRT-UTJ) = -2.331 + 0.000X1 + 0.040X2 + 0.820X3, where X1 is the travel cost variable, X2 is the travel time variable and X3 is the waiting time variable. The conclusion obtained from the results of this study is that the MRT is the most preferred mode of public transportation compared to Transjakarta in this new normal era. Research limitations/implications: Although most of the enterprises surveyed have an idea how to respond to calamities and mitigate disastrous situations, this research argues that a solid policy framework might be drawn through the local government units concerned to institutionalized this effort. Practical implications: The convenience factor is the main factor for public transport users to choose the MRT, while the travel cost factor is the main factor for public transport users to choose Transjakarta. Originality/value: This paper is an original work. Paper type: Research paper